The effectiveness of training programmes as percieved by support staff in Universiti Putra malaysia - Tan, Sai Tian (1998)
The research project has been designed with the primary aim of establishing the effectiveness of the training programmes as perceived by employees who have undergone training. More specifically, it seeks to evaluate the effectiveness of training programme for the support staff in UUM. This study examines the extent of effectiveness of the training programmes with respect to reaction, learning and behaviour outcomes. The survey investigates whether the effectiveness level vary according to trainee's personal characteristics (age, educational level, working experience and number of years of service at current job). A study sample of hundred and thirty six (136) was drawn from the support staff (administration) of Universiti Utara Malaysia. A hundred and six (106)support staff responded to the survey. Data were collected using self-administrated questionnaires personally distributed by the researcher. Completed questionnaires were picked up three weeks from the date the questionnaires were distributed.